Distribution extension of the spectacled petrel (Procellaria conspicillata) off the argentine continental shelf and oceanic adjacent waters - Hernandez, Maximiliano Manuel (2019)
The Spectacled Petrel Procellaria conspicillata is endemic of the Tristan da Cunha Archipelago, in the South Atlantic Ocean. However, it is scarcely detected in waters off Argentina beyond its traditional distribution along the southwest Atlantic during the breeding season. This study compiles distributional records of Spectacled Petrel for the target area (chiefly between 38°S to 46°S and 23°W to 57°W) obtained in situ, from non-systematic observations at sea, between 2015 and 2018 (totaling 4 trips); and by literature review. Nineteen new sightings of the species are presented. In 46 sightings a total of 65 individuals were recorded chiefly within waters of the Argentine continental shelf (< 200 m) (46%) and oceanic adjacent waters (54%). The bulk of the sightings (95%) were obtained during the species breeding season. In addition, we report the southernmost record of the species in oceanic waters for the southwest Atlantic (46o10'S; 57o06'W).